Clap-Trap Tweets and Epideictic Episodes : Two Years of Evaluative Praise from President Trump - ROE, DARRELL L (IJRDO - Journal of Social Science and Humanities Research, 2019)
This two-part study content analyzed tweets sent by President Donald Trump during the first two years of his presidency. Part One analyzed the epideictic (praise and blame) nature of 7,290 tweets sent over 819 days (just over two years and two months) about administration and cabinet members who quit or were fired during this time period. Part Two analyzed the 6,291 praise tweets sent over 731 days (first two years exactly) used to manipulate various individuals and groups. The praise tweets were broken down into eleven subcategories and content analyzed according to their intended targets and how the tweet was designed to manipulate. The concept of “mass self-communication,” as used by Castells (2009), is utilized as the theoretical foundation for examining the prolific nature of the president’s dominant online rhetoric.